2017
DOI: 10.1371/journal.pone.0180248
|View full text |Cite
|
Sign up to set email alerts
|

What is the level of evidence for the amnestic effects of sedatives in pediatric patients? A systematic review and meta-analyses

Abstract: BackgroundStudies have suggested that benzodiazepines are amnestic drug par excellence, but when taken together, what level of evidence do they generate? Are other sedatives as amnestic as benzodiazepines? The aim of this study was to assess the level of scientific evidence for the amnestic effect of sedatives in pediatric patients who undergo health procedures.MethodsThe literature was searched to identify randomized controlled trials that evaluated anterograde and retrograde amnesia in 1-19-year-olds who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 69 publications
0
10
1
1
Order By: Relevance
“…It is noteworthy that there was an improvement regarding the reduction in the percentage of struggling behavior from the first to the second visit, which was remarkable in older children at G1. This is probably due to the amnestic properties of the midazolam, which is able to produce loss of memory of procedures (5). In fact, a previous study demonstrated that 0.2 mg/kg of intranasal midazolam in combination with nitrous oxide produced more anterograde amnesic effects evaluated by a recall test for children 24-28 months old during dental treatment compared with 3.7 mg/kg of hydroxyzine (21).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is noteworthy that there was an improvement regarding the reduction in the percentage of struggling behavior from the first to the second visit, which was remarkable in older children at G1. This is probably due to the amnestic properties of the midazolam, which is able to produce loss of memory of procedures (5). In fact, a previous study demonstrated that 0.2 mg/kg of intranasal midazolam in combination with nitrous oxide produced more anterograde amnesic effects evaluated by a recall test for children 24-28 months old during dental treatment compared with 3.7 mg/kg of hydroxyzine (21).…”
Section: Discussionmentioning
confidence: 97%
“…Although sedated children may show more controllable behavior compared to placebo (3), it is known that sedation can fail in guiding children's behavior in some cases (4). On the other side, drugs such as midazolam promote anterograde amnesia, a desirable sedative effect when dealing with pediatric patients (5).…”
Section: Crossover Studies Of Pediatric Dental Sedation Are Inapproprmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketamine, benzodiazepines, barbiturates, chloral hydrate, antihistamines, narcotics, nitrous oxide, dexmedetomidine, Propofol, and melatonin have been administered for dental sedation, with limited research for most regarding the incidence of amnesia [9]. Factors associated with amnesia include patient characteristics, level of sedation, and the method used to evaluate amnesia [10].…”
Section: Of 13mentioning
confidence: 99%
“…Factors associated with amnesia include patient characteristics, level of sedation, and the method used to evaluate amnesia [10]. Establishing memory and recall in the pediatric population is challenging, with quantitative methods most frequently employed [9,11,12].…”
Section: Of 13mentioning
confidence: 99%